The temperature inside football helmets during head impact: a five-year study of collegiate football games. (March 2013) - Rowson, Steven; Duma, Stefan M
The objective of this study was to measure in-helmet temperature at the time of impact in a large cohort of football players, as such data can provide new insight to the temperatures helmets should be evaluated at during experimental testing that assess helmet safety. A large cohort of Virginia Tech football players were instrumented with the HIT System (Simbex, Lebanon, NH, USA), which recorded in-helmet temperature and head acceleration for head impacts experienced during 60 games between 2006 and 2010. The average in-helmet temperature at time of impact was 76.4 °F ± 10.1 °F (24.6 °C ± 5.6 °C). In-helmet temperature was strongly correlated to the ambient temperature of the game. Head acceleration resulting from impact varied less than 10% across temperatures, and temperature did not significantly influence head acceleration. These data have implications for the testing conditions used in the laboratory when evaluating the safety of helmets.